Explaining the Size Differences of Exporter Productivity Premia: Theory and Evidence - Ingo Geishecker; Philipp J.H. Schröder; Allan Sörensen (Center for Economic Studies and ifo Institute (CESifo), 2014)
Why is it that exporter productivity premia (EPP) differ so widely in size? We take this question to the theory and to the data. We derive the sectoral EPP in a standard heterogeneous firms trade model and apply the insights from the model to 13 years of data for all Danish manufacturing firms. We show that a significant share of the observed variation in EPPs across sectors, and hence across countries, can be explained by the variation in productivity dispersion, trade costs and the elasticity of substitution.
Keywords: F12; F14; D24; O47; 330; intra-industry trade; exporter productivity; firm-level data; heterogeneous firms